Increasing mustard (Brassica juncea L.) yields through exposure sound and preventive pest management based on refugia plants - Asritanarni Munar; Widihastuty Widihastuty; Rini Susanti; Muhammad Hanafi; Imam Hartono Bangun (Agro Bali : Agricultural Journal, 2023)
Abstract. In Indonesia, mustard plants will increase by 8.2% in 2021, but more than that is needed to meet the community's needs due to a growing population. Pests and fertilization problems hinder expected growth.  The provision of plant fertilizers can be replaced through the application of sound. Exposure sounds to plants can increase plant growth by opening stomata, improving water absorption, and increasing plant nutrient uptake. This study aimed to examine the application of sound effects and refugia plants t890po increase the growth and yield of mustard greens (Brassica juncea L.). The study used a Time's Series Randomized Block Design with 3 replications. The first factor is sound applications (S) consisting of S0 = without sound, S1 = rock music (Frequency 21-14,000 Hz), and S2 = classical sound (Frequency 21-14,000 Hz). The second factor is the refugia plant (R) consisting of R0 = without refugia, R1 = Tagetes erecta L., R2 = Zinnia elegans L, and R3 = Ocimum bassilicum L. The application of classical sound frequency (20-14,000 Hz) affects the growth process of mustard plants through the increase in plant height (14.5%), leaf area (20.92%), wet weight (3.5%), dry weight (26.41%), total chlorophyll (11.62%) and plant N content (31.03%). Meanwhile, rock music frequency (20-14,000 Hz) can increase plant height (2.97%), leaf area (19.11%), and total stomata (9.6%). Refugia plants affect the process of plant protection through their ability to attract pests in the research area.